2019
DOI: 10.3390/polym11121989
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Insights into Sequence Distributions and Conformation-Dependent Properties of High-Phenyl Polysiloxanes

Abstract: The excellent performance and wide applications of phenyl polysiloxanes are largely due to their phenyl units and monomer sequences. However, the relationship between molecular structure and material properties has not been explicitly elucidated. In this work, the sequence distribution and microstructure of random copolymers were quantitatively investigated by means of a molecular dynamics (MD) simulation combined with experimental verification. The results of 29Si NMR showed that the large number of phenyl un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 46 publications
(67 reference statements)
0
5
0
Order By: Relevance
“…The properties of the PDMS- co -PDPS copolymer are greatly dependent on the amounts of diphenyl component . Zhu et al showed that incorporation of a high mole percentage of phenyl components changes the atomic structures significantly . Other structural changes have also been observed in other copolysiloxanes. Moreover, our recent molecular simulation study clarified the structure–property interplay of the PDMS- co -PDPS copolymer and showed that the increase of the diphenyl component greatly slows down microscopic relaxation, which can affect the bulk viscoelasticity of the copolymer according to the literature …”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…The properties of the PDMS- co -PDPS copolymer are greatly dependent on the amounts of diphenyl component . Zhu et al showed that incorporation of a high mole percentage of phenyl components changes the atomic structures significantly . Other structural changes have also been observed in other copolysiloxanes. Moreover, our recent molecular simulation study clarified the structure–property interplay of the PDMS- co -PDPS copolymer and showed that the increase of the diphenyl component greatly slows down microscopic relaxation, which can affect the bulk viscoelasticity of the copolymer according to the literature …”
Section: Introductionmentioning
confidence: 58%
“…26 Zhu et al showed that incorporation of a high mole percentage of phenyl components changes the atomic structures significantly. 27 Other structural changes have also been observed in other copolysiloxanes. the PDMS-co-PDPS copolymer and showed that the increase of the diphenyl component greatly slows down microscopic relaxation, which can affect the bulk viscoelasticity of the copolymer according to the literature.…”
Section: Introductionmentioning
confidence: 79%
“…Additionally, the flexibility of the Si−C and Si−O−Si structures in the cross-linkers increases the mobility of the cross-linked network, thereby reducing the material's T g . 34 Although this property of silanes and siloxanes is beneficial for producing flexible materials such as elastomers, it poses a disadvantage for electronic packaging applications. Nonetheless, the T g of these three cross-linked samples has reached the level of commonly used high-T g epoxy-based FR-4 substrates, 35 indicating that the materials obtained in this study can still meet typical application requirements.…”
Section: Resultsmentioning
confidence: 99%
“…This is first due to the lower functional group content of the silicon-containing cross-linkers (two functional groups per molecule) compared to the two control cross-linkers (three or more functional groups per molecule), resulting in a relatively lower cross-link density of the products. Additionally, the flexibility of the Si–C and Si–O–Si structures in the cross-linkers increases the mobility of the cross-linked network, thereby reducing the material’s T g . Although this property of silanes and siloxanes is beneficial for producing flexible materials such as elastomers, it poses a disadvantage for electronic packaging applications.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Zhu et al showed the influence of the phenyl units on the atomic structures of the methyl- co -phenyl polysiloxane, with moderately high phenyl ratios of 31.6 mol% and 30.7 mol% for PDMS- co -PMPS and PDMS- co -PDPS, respectively. 33 However, most of the previous works focus on exploring the structural and mechanical properties separately and pay less attention to their connection. Consequently, the interplay between the two properties is not well understood, especially for cases with high phenyl content, thus leaving an understanding of the influence of the phenyl content on the properties of the copolymer somewhat unclear.…”
Section: Introductionmentioning
confidence: 99%